The Dose-Dependent Effects of Fluorocitrate on the Metabolism and Activity of Astrocytes and Neurons - Huiling Zhuang; Deliang Yuan; Fuxiu Shi; Xujun Wu; Zhen Luo; Wenbiao Gan (Brain Sciences)
Background: Fluorocitrate (FC) ranging from 5 μM to 5 mM is often used as a specific metabolic inhibitor of the astrocytes to study astrocytic functions. Whether FC at such concentrations may affect neuronal metabolism and function in vivo remains unclear. Methods: We examined the effects of FC on the ATP levels and Ca2+ activity of the astrocytes and neurons in the motor cortices of living mice using two-photon microscopy. Results: We found that 25 μM and 250 μM of FC decreased the intracellular ATP levels and Ca2+ activity in the astrocytes in the motor cortex. Equally, 250 μM of FC, but not 25 μM of FC, reduced the intracellular ATP levels in the dendritic processes of the layer 5 pyramidal neurons. However, 25 μM of FC increased the neuronal Ca2+ activity, whereas ≥250 μM of FC decreased it. To test whether the differential effects of FC on neuronal Ca2+ activity reflect the direct effect of FC on the neurons or its indirect effect on the astrocytes, we used the CNO-hM3Dq chemogenetic approach to block astrocytic Ca2+ activity and examined the effect of FC. In the absence of astrocytic Ca2+ activity, 25 μM of FC still increased and ≥250 μM of FC reduced the dendritic Ca2+ activity of the neurons, respectively, suggesting a direct effect of 250 μM of FC on inhibiting neuronal Ca2+ activity. Further, 250 μM, but not 25 μM, of FC increased the size of the dendritic spines over 2 h. Conclusions: Our findings suggest that FC at high concentrations (≥250 μM) is not a specific inhibitor of astrocytic functions, as it directly affects neuronal metabolism and synaptic plasticity in vivo.